It's time to rein in the fed - Scott Fullwiler; L. Randall Wray (Levy Economics Institute of Bard College, 2011)
Scott Fullwiler and Senior Scholar L. Randall Wray review the roles of the Federal Reserve and the Treasury in the context of quantitative easing, and find that the financial crisis has highlighted the limited oversight of Congress and the limited transparency of the Fed. And since a Fed promise is ultimately a Treasury promise that carries the full faith and credit of the US government, the question is whether the Fed should be able to commit the public purse in times of national crisis.
Keywords: 330